Clinical Significance of Lymph Node Metastasis in the Mesentery of the Terminal Ileum in Patients With Right-sided Colon Tumors at Different Locations. Issue 6 (June 2018) - Kang, Sung Il; Kim, Duck-Woo; Shin, Eun; Kim, Myung Jo; Son, Il Tae; Oh, Heung-Kwon; Kang, Sung-Bum
Abstract : BACKGROUND: There are limited reports on peri-ileal lymph node metastasis in patients with right-sided colon cancer, and little is known about their clinical significance. OBJECTIVE: This study aimed to examine the role of tumor location in the prevalence and clinical significance of peri-ileal lymph node metastasis in patients with right-sided colon cancer. DESIGN: This is a retrospective study from a prospective cohort database. SETTINGS: The study was conducted at a tertiary referral hospital. PATIENTS: Patients with right-sided colon cancer treated with radical surgery in a hospital between May 2006 and September 2016 were included. MAIN OUTCOME MEASURES: The frequency of peri-ileal lymph node metastasis in the study cohort and the role of tumor location and the clinical characteristics of patients with peri-ileal lymph node metastasis were determined. RESULTS: We examined 752 cases with right-sided colon cancer including 82 cecal, 554 ascending colon, and 116 hepatic flexure cancer. Twenty patients (2.7%) had peri-ileal lymph node metastasis. The incidence of metastasis to peri-ileal lymph nodes was 7.3% (6/82) in patients with cecal cancer, 2.2% (12/554) in patients with ascending colon cancer, and 1.7% (2/116) in patients with hepatic flexure cancer. Three patients had stage III cancer and 17 had stage IV. All 3 patients with positive peri-ileal lymph nodes and stage III cancer had cecal tumors. In contrast, all patients with ascending colon or hepatic flexure cancer and positive peri-ileal lymph nodes had stage IV cancer. LIMITATIONS: The results were limited by the retrospective design of the study and the small number of patients with peri-ileal lymph node metastasis. CONCLUSIONS: Peri-ileal lymph node metastasis was rare even in right-sided colon cancer and occurred mainly in stage IV. However, it occurred in some patients with locally advanced cecal cancer. These results suggest that optimal resection of the mesentery of the terminal ileum might have clinical benefit, especially in curative surgery for cecal cancer. SeeVideo Abstract athttp://links.lww.com/DCR/A556 .